Pain Control and Functional Milestones in Total Knee Arthroplasty: Liposomal Bupivacaine versus Femoral Nerve Block. Issue 1 (January 2017) - Yu, Stephen; Szulc, Alessandra; Walton, Sharon; Bosco, Joseph; Iorio, Richard
Abstract: Background: Although pain management after total knee arthroplasty (TKA) affects rehabilitation, length of stay, and functional outcomes, pain management for patients undergoing TKA has yet to be standardized. Femoral nerve blocks (FNBs) are commonly used as an adjunct; however, these can result in transient quadriceps weakness and have been associated with in‐hospital falls. Periarticular infiltration of liposomal bupivacaine has been recently introduced as a long‐acting analgesic that can be administered without affecting motor function. Questions/purposes: (1) Does periarticular liposomal bupivacaine compared with FNB result in improved pain control as measured by pain scores and narcotic consumption? (2) How do liposomal bupivacaine and FNB compare in terms of gait and stairclimbing milestones and the proportion of patients who experienced a fall in the hospital? Methods: Between September 2013 and October 2014, a retrospective analysis was conducted involving 24 surgeons who performed a total of 1373 unilateral, primary TKAs. From September 2013 to April 2014, the routine approach to TKA pain management pathway consisted of preoperative administration of oral analgesics, intraoperative anesthesia (preferred spinal or general), an ultrasound‐guided FNB, intraoperative analgesic cocktail injection, patient‐controlled analgesia, and oral and IV narcotics for pain as needed. A total of 583 patients were included in this study group. Starting May 2014, FNBs were discouraged and there was department‐wide adoption of liposomal bupivacaine. Liposomal bupivacaine became routinely used in all patients undergoing TKA with no other changes made to the multimodal analgesia protocol at that time, and 527 patients in this study group were compared with the FNB cohort. Chart review on a total of 1110 patients was conducted by a research assistant who was not participating in patient care. During the inpatient stay, pain scores during 8‐hour intervals, narcotic use, and physical therapy milestones were compared. Results: With the numbers available, we detected no clinically important difference in pain scores throughout the hospital stay; however, patients treated with liposomal bupivacaine consumed very slightly less narcotics overall (96 ± 62 versus 84 ± 73 eq mg of morphine; [95% confidence interval, 11‐13 mg]; p = 0.004) through postoperative Day 2 of inpatient hospitalization. Seventy‐seven percent (406 of 527) of patients receiving liposomal bupivacaine achieved their gait milestones of clearing 100 feet of ambulation versus 60% (349 of 583) of patients receiving FNB (p < 0.001) before discharge. Likewise, 94% (497 of 527) of patients receiving liposomal bupivacaine completed stairs compared with 73% (427 of 583) of patients receiving FNB (p < 0.001). Patients who received liposomal bupivacaine were less likely to experience a fall during the hospital stay than were patients treated with FNB (3 of 527 [0.6%] versus 12 of 583 [2%]; p = 0.03). Conclusions: In the absence of strong data supporting FNB over liposomal bupivacaine, we have modified our TKA pain management protocols by adopting liposomal bupivacaine in lieu of FNBs, facilitating rapid rehabilitation while providing adequate pain control. Level of Evidence: Level III, therapeutic study.